FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN DI PERUSAHAAN PERKEBUNAN KELAPA SAWIT PT. MUSAM UTJING - Kaezia Karolin Tambunan; T Dalmiyatun; S Satmoko (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2019)
Oil palm plantations have an important role in Indonesia. PT. Musam Utjing as one of many oil palm plantation companies in Indonesia must improve its employee performance to be able to compete with similar industries. This research aims to describe the factors that can affect PT. Musam Utjing’s employee performance, describe PT. Musam Utjing’s employee performance, and analyze the effect of salary, incentives, motivation, work environment, training and development on PT. Musam Utjing’s employee performance. The research was conducted at PT. Musam Utjing, Langkat Regency, North Sumatra. The research method was a survey method that includes observation and interview. The were 69 samples on this research calculated by using Slovin formula. Sampling was done by using cluster sampling technique. Data analysis used includes descriptive analysis and multiple linear regression analysis using SPSS. The results of the study show that the performance of PT. Musam Utjing employees is good. The factors that can affect the employee performance with the highest category are motivation and training and development. Salary, incentives, motivation, work environment, training and development simultaneously affect the performance of PT. Utjing Musam employees, where incentives, motivation, training and development partially affect the performance of PT. Musam Utjing employees.